Phenotypic Characterization, Evaluation, and Classification of Cassava (Manihot esculenta Crantz) Accessions in Ethiopia - Berhanu Bilate Daemo; Derbew Belew Yohannes; Tewodros Mulualem Beyene; Wosene Gebreselassie Abtew (International Journal of Agronomy)
Cassava has a crucial role in benefiting smallholder farmers as the main food and income source in southern Ethiopia. Characterization accessions are crucial for assessing variation, classifying, and identifying desirable accessions for crop improvement and conservation. In this regard, there needs to be more information on the morphological characterization and classification cassava accessions. Thus, the aim of this research was to systematically characterize, evaluate, and classify cassava accessions using qualitative characters to provide useful information for breeding program and conservation. A total of 64 accessions were planted using a simple lattice design during the 2020-2021 cropping season. Thirty qualitative data were collected at 3, 6, 9, and 18 months after planting and analyzed using the SAS and R-software packages. The high variable characteristics were the shape of the central leaflet, petiole color, leaf retention, branching habit, the color of the stem epidermis, the color of the stem exterior, the external color of the storage root, and the color of the root pulp towards frequency distribution analysis. The Shannon–Weaver diversity index ranged from 0.24 to 1.47, with an overall mean of 0.84. The first three dimensions in the multiple correspondent method explained approximately 39.39% of the total variation, with Dim 1 accounting for 20.77% and Dim 2 accounting for 9.98%, while petiole color and texture of the root epidermis were the leading contributors to the total variation, respectively. In clustering analysis, 64 accessions were classified into 4 clusters of varying sizes. The distribution of accessions in each cluster revealed that 52 accessions were in cluster I, 6 in cluster II, 5 in cluster III, and 1 in cluster IV. Each cluster was varied by a major group characteristic that it represented. Furthermore, the study identified the desirable accessions for desired storage root characteristics such as root constrictions, the external color of the storage root, the color of root pulp, the color of the root cortex, and cortex peeling tendency. In conclusion, the various analyses performed indicated the existence of sufficient genetic variability for the characteristics evaluated, which could be attributed to the dissimilar genetic backgrounds of the evaluated accessions. Thus, these could be utilized for breeding work and conservation.